2018
DOI: 10.1542/peds.2018-0442
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-to-Home Interventions, Use, and Satisfaction: A Meta-analysis

Abstract: Hospital-to-home transitions are critical opportunities to promote patient safety and high-quality care. However, such transitions are often fraught with difficulties associated with increased health care use and poor patient satisfaction. OBJECTIVE: In this review, we determine which pediatric hospital discharge interventions affect subsequent health care use or parental satisfaction compared with usual care. DATA SOURCES: We searched 7 bibliographic databases and 5 pediatric journals. STUDY SELECTION: Inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 101 publications
0
28
0
1
Order By: Relevance
“…Randomized controlled pragmatic clinical trial evaluating the effectiveness of a discharge follow-up phone call on 30-day hospital readmissions: balancing pragmatic and explanatory design considerations. BMJ Open,8(2) Hamline, M. Y., Speier, R. L., Vu, P. D., Tancredi, D., Broman, A. R., Rasmussen, L. N., Tullius, B. P., Shaikh, U., & T. Li, S.-T. (2018 readmissions in adult patients with heart failure. Some future study is required to establish the optimal education content, delivery method, intensity, and timing.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Randomized controlled pragmatic clinical trial evaluating the effectiveness of a discharge follow-up phone call on 30-day hospital readmissions: balancing pragmatic and explanatory design considerations. BMJ Open,8(2) Hamline, M. Y., Speier, R. L., Vu, P. D., Tancredi, D., Broman, A. R., Rasmussen, L. N., Tullius, B. P., Shaikh, U., & T. Li, S.-T. (2018 readmissions in adult patients with heart failure. Some future study is required to establish the optimal education content, delivery method, intensity, and timing.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to post discharge telephone calls, patient and family education with the teachback method is used in the hospital and after the patient is discharged to reinforce care and reduce readmissions (Almkuist, 2017;Coller et al, 2018;Hamline et al, 2018;Shermont et al, 2016;Yiadom et al, 2018). Shermont et al (2016) suggested that the teach-back methodology be implemented by all staff to support the improvement of patient education.…”
Section: Education With Teach-backmentioning
confidence: 99%
See 3 more Smart Citations